2019
DOI: 10.3389/fvets.2019.00303
|View full text |Cite
|
Sign up to set email alerts
|

A Case for Eustress in Grazing Animals

Abstract: Herbivores grazing in extensive systems are exposed to a series of challenges, rooted in the inherent spatial and temporal variability of their environment that potentially constrain their health, nutrition, and welfare. Nevertheless, in this review, we argue that challenges induced by some biotic (e.g., vegetation) and abiotic (e.g., terrain) factors may also be viewed as “positive” sources of stress or eustress, since they present complex problems, that when solved successfully elicit a greater degree of beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Strategic supplementation of livestock on pasture with industrial by-products, inedible to humans (Sunvold et al, 1991;Macdonald et al, 2007), also has potential to increase the carrying capacity of pasture-based grazing systems and mitigate potential welfare issues associated with feedlots, such as reduced ability to express natural behavior and self-selection of diets (Atwood et al, 2001;Villalba and Manteca, 2019). For example, feeding limited amounts of phytochemically-rich fruit and vegetable by-products such as leaves, pomace, peels, rinds, pulp, seeds, and stems (Sruamsiri, 2007;Wadhwa and Bakshi, 2013;Salami et al, 2019) to livestock on pasture can potentially mitigate some nutritional deficits, decrease environmental impacts, and reduce the of risk of overgrazing and land unavailability, while enhancing the phytochemical richness of meat and milk (Provenza et al, 2003(Provenza et al, , 2019Salami et al, 2019).…”
Section: Suitability and Scalability Of Pasture-based Livestock Systemsmentioning
confidence: 99%
“…Strategic supplementation of livestock on pasture with industrial by-products, inedible to humans (Sunvold et al, 1991;Macdonald et al, 2007), also has potential to increase the carrying capacity of pasture-based grazing systems and mitigate potential welfare issues associated with feedlots, such as reduced ability to express natural behavior and self-selection of diets (Atwood et al, 2001;Villalba and Manteca, 2019). For example, feeding limited amounts of phytochemically-rich fruit and vegetable by-products such as leaves, pomace, peels, rinds, pulp, seeds, and stems (Sruamsiri, 2007;Wadhwa and Bakshi, 2013;Salami et al, 2019) to livestock on pasture can potentially mitigate some nutritional deficits, decrease environmental impacts, and reduce the of risk of overgrazing and land unavailability, while enhancing the phytochemical richness of meat and milk (Provenza et al, 2003(Provenza et al, , 2019Salami et al, 2019).…”
Section: Suitability and Scalability Of Pasture-based Livestock Systemsmentioning
confidence: 99%
“…Several studies have shown that the challenges induced by biotic factors (such as changes in vegetation and heat) may be a source of animal stress, eliciting a greater degree of behavioral plasticity and adaptability in grazing animals (Villalba and Manteca, 2019). The results obtained from our experiments show a downregulation in the P60 group of different lipid classes such as phosphocoline, lysophosphocoline and phosphoethanolamines.…”
Section: Discussionmentioning
confidence: 99%
“…Offering by-products on pasture, as opposed to feeding them to cattle in feedlots, would also mitigate some of the animal welfare issues associated with feedlots such as unfamiliar environments, inability to self-select their diet, and the ability to express natural behavior (Atwood et al, 2001;Villalba and Manteca, 2019). Offering by-products to cattle on pasture may represent a worthwhile opportunity for the livestock industry to improve consumer perception while maintaining the ability to upcycle by-products to meet customer demand.…”
Section: The Ecological Impacts Of Plant-based Meat Vs Meat Consumptionmentioning
confidence: 99%